2020
DOI: 10.12973/eu-jer.9.2.685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skills Development in Brunei Trainee Teachers: Intervention Implications

Abstract: Teacher education has been innovated in Brunei to support the ongoing inclusive education and curriculum reforms. This survey investigated the development of essential instructional skills in initial Brunei trainee teachers. The sample consisted of 109 student teachers (71 females and 38 males). Significant mean scores (Mean ≥ 4, p< .05) and 95% confidence intervals were used to identify the levels of proficiency and enablers of success in teaching. Participants were proficient on 15 of the 28 skills measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…The results of the current study show similarity with the previous research conducted by Mundia (2020). Its participants, who were trainee teachers, also considered themselves competent in listening to others and showing respect.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the current study show similarity with the previous research conducted by Mundia (2020). Its participants, who were trainee teachers, also considered themselves competent in listening to others and showing respect.…”
Section: Discussionsupporting
confidence: 86%
“…The empirical data showed that the most developed skills, in students' opinion, are critical thinking and problemsolving. Mundia (2020) investigated the development of essential instructional skills in initial Brunei trainee teachers. One of the research objectives was to determine the skill areas in which Arab World English Journal www.awej.org ISSN: 2229-9327 303 pre-service teachers considered themselves competent.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Assessment plays a vital role in education because it is used to identify what teachers must do to improve and develop students' abilities (Darling-Hammond et al, 2020;Puspitasari, 2016). Also, assessment is one of the five important classroom learning components (Mundia, 2020). Teachers and their activities are the most crucial variables in the learning scheme (Ahmad, 2020).…”
Section: Introductionmentioning
confidence: 99%